Hasil Belajar Kewirausahaan Ditinjau Dari Kedisiplinan Belajar Dan Kemampuan Berpikir Kritis Pada Siswa Kelas X Smk Muhammadiyah Kartasura Tahun Ajaran 2015/2016 - Wibowo, Erwan Ramadhan Ari, Drs. Sudarto, M.M (2016)
The purpose of this research are: 1) Whether there was an effect on learning outcomes learning discipline of entrepreneurship. 2) Is there any influence critical thinking skills to the learning outcomes of entrepreneurship. 3) Is there any influence of learning discipline and critical thinking skills to the learning outcomes of entrepreneurship. This research is descriptive quantitative research with a conclusion through statistical methods. The population in this study were all students of class X SMK Muhammadiyah Kartasura academic year 2015/2016. samples are taken as 114 students by random sampling propotionate. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability were tested. Data analysis technique used is multiple linear regression analysis, t-test, F, and the relative contribution and effective. The results of the regression analysis obtained regression equation: Y = 45.746 + 0.500 X1 + 0.408 X2. The equation shows that the entrepreneurial learning outcomes are influenced by the discipline of learning and critical thinking skills. The conclusions drawn are: 1) Discipline entrepreneurship learning to the learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, 7.071> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 71% and the effective contribution of 28.8%. 2) The ability to think critically about the entrepreneurial learning outcomes are acceptable. This is based on multiple linear regression analysis (t test) note that tcount> ttable, namely 4.285> 2.000 and the significance value <0.05, namely 0.000 with the relative contribution of 29% and the effective contribution of 11.8%. 3) Discipline learning and critical thinking skills to the learning outcomes of entrepreneurship acceptable. This is based on multiple linear regression analysis of variance (F test) is known that F count> F table, ie 37.922> 3.150 and the significance value <0.05, namely 0.000. 4) The coefficient of determination (R2) of 0.406 indicates that the influence of the discipline of learning and critical thinking skills to the learning outcomes of entrepreneurship is 40.6%, while the rest influenced by other variables.